Perbandingan Kadar HB Sebelum dan Sesudah Pengobatan Oat Fase Intensif pada Penderita Tuberkulosis Paru di Puskesmas Petanahan Kebumen Tahun 2021: The Comparison of Hemoglobin Levels Between Before and After Treatment of Intensive Phase of Anti-Tuberculosis Drug in Pulmonary Tuberculosis Patients of Petanahan Public Health Care Center, Kebumen Regency - Evi Nurhayati; Arif Mulyanto; Tantri Analisawati Sudarsono; Linda Wijaya (Jurnal Surya Medika (JSM), 2023)
Treatment of tuberculosis with main anti-tuberculosis drugs (OAT) includes isoniazid (INH), rifampin (RIF), ethambutanol (EMB), streptomycin (SM), and pyrazinamide (PZA). Although most Anti-Tuberculosis Drugs (OAT) are acceptable in therapy, they have potential side effects, including the side effects of hematological reactions such as anemia. This study's purpose was to compare HB levels before and after the intensive phase of Anti-Tuberculosis Drugs treatment in TB patients at Petanahan Public Health Care Center, Kebumen Regency. This was an analytic observational study with a cross-sectional design. The sample in this study was 28 people. The result showed that the average Hb level of pulmonary TB patients at Petanahan Public Health Care Center before and after the treatment were 11.05 g/dl and 11.6 g/dl, respectively. Therefore there was an effect of comparing Hb levels before and after the intensive phase of Anti-Tuberculosis Drugs treatment in pulmonary TB patients at the Petanahan Public Health Center in 2021. The increase in the average Hb levels of patients with pulmonary TB before and after the treatment was 0.55. The sig values obtained from the analysis of Hb levels before and after the treatment were a = 0.200 (p0.005) and 0.023, respectively. Due to the P value (0.023 < 0.05), Ho was rejected. It meant that there was a difference in Hb levels before and after the Intensive Phase of Anti-Tuberculosis Drugs treatment in patients with pulmonary TB at Petanahan Public Health Care Center, Kebumen Regency.